Digital learning communities : investigating the application of social software to support networked learning (CG6-36). - Fitzgerald, Robert; Steele, James (Australian Learning and Teaching Council, 2008)
The Digital Learning Communities (DLC) Project considered the potential of social software to support peer engagement and group learning in higher education. The project established a series of pilots that examined ways in which social software could provide students with opportunities to engage with their peers to supplement the more formal aspects of their education. It spoke with teaching and support staff about the use of social software to support learning, and to students about how they saw social software being used in their university lives. It established a wiki-based cookbook that provides ideas and suggestions for the use of social software, and conducted surveys of staff and students' use of new social technologies. [Executive summary, ed]